Cranial imaging window implantation technique for longitudinal multimodal imaging of the brain environment in live mice - Davide Croci; Anoek Zomer; Joanna Kowal; Johanna A. Joyce (STAR Protocols, 2023)
Summary: Intravital two-photon microscopy of the mouse brain requires visual access without affecting normal cognitive functions, which is crucial for longitudinal imaging studies that may last several months. In this protocol, we describe the surgical implantation of a metal-free cranial imaging window, which can be used to perform two-photon microscopy and magnetic resonance imaging in the same animal. This multimodal imaging platform enables the investigation of dynamic processes in the central nervous system at a cellular and macroscopic level.For complete details on the use and execution of this protocol in the context of brain cancer, please refer to Zomer et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.